2008
DOI: 10.1089/scd.2007.0107
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of SNEV Causes Defects of Hematopoietic Stem Cells Functions

Abstract: The quality of hematopoietic stem cells (HSCs) is essentially defined by two characteristics, i.e., multilineage differentiation and self-renewal capacity. Thus, it is of high priority to clarify mechanisms that regulate these functions and to understand them at the molecular level. In the present study, we investigated the role of senescence evasion factor (synonymously hPrp19,hPSO4,hNMP200: SNEV), a multifunctional protein involved in pre-mRNA splicing, regulation of replicative life span, and DNA repair. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In recent years, increasing evidence suggests that hematopoietic stem and progenitor cells (HSCs) are affected by the aging process similarly to all other somatic cells (de Haan, Nijhof, & Van Zant, 1997;Rossi et al, 2005). Additionally, based on data derived from myeloid secondary colony formation assays, we could recently show that the proliferative capacity of murine HSCs is closely associated with the expression of the senescence evasion factor (SNEV) (Schraml et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…In recent years, increasing evidence suggests that hematopoietic stem and progenitor cells (HSCs) are affected by the aging process similarly to all other somatic cells (de Haan, Nijhof, & Van Zant, 1997;Rossi et al, 2005). Additionally, based on data derived from myeloid secondary colony formation assays, we could recently show that the proliferative capacity of murine HSCs is closely associated with the expression of the senescence evasion factor (SNEV) (Schraml et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…In addition to being involved in spliceosome assembly and stabilization, SNEV regulates proteasome function due to its U3-ligase activity, and is involved in DNA repair (Grillari et al, 2010). Furthermore, the haploinsufficiency of SNEV has been demonstrated using a heterozygous mouse model, which showed that the proliferative and repopulating capacity of hematopoietic stem cells from these mice was clearly compromised (Schraml et al, 2008). …”
Section: Splicing Factors Involved In Endothelial Senescencementioning
confidence: 99%
“…To merge the different names of SNEV that derive from the yeast homologue that were synonymously termed Pso4 as well as Prp19, we suggest here to use SNEV Prp19-Pso4 . Knock-out of SNEV Prp19-Pso4 in mice is early embryonic lethal, whereas embryonic fibroblasts from heterozygous SNEV Prp19-Pso4+/− mice show reduced replicative life span (23) and hematopoietic progenitor defects in proliferation and self-renewal (24). This effect might be due to its additional function as a DNA repair factor (25, 26), especially in interstrand cross-link repair, where it interacts with WRN, the protein mutated in the premature progeroid Werner syndrome (27).…”
mentioning
confidence: 99%